Prevalence of Helicobacter pylori in Patients With Brucellosis. (1st August 2012) - Esen, Ramazan; Dulger, Ahmet Cumhur; Begenik, Huseyin; Demirtas, Levent; Ebinc, Senar; Aytemiz, Enver; Sunnetcioglu, Mahmut; Aslan, Mehmet
Abstract : Background: Helicobacter pylori infection affects approximately 40 million individuals in Turkey. Our prefecture is an endemic area for H. pylori infection and brucellosis. However, there are no data on the H. pylori prevalence among patients with brucellosis. Objectives: The primary aim of the current study was to investigate the link between H. pylori infection and brucellosis. The secondary aim was to determine the seroprevalence of H. pylori infection in healthy individuals. Methods: Between May 2010 and May 2011, serum was collected from patients with Brucella infection (n = 111) and healthy individuals (n = 120) and analyzed using an enzyme-linked immunosorbent assay kit. Brucella infection was defined as a positive Wright test or blood culture positivity for Brucella in conjunction with disease symptoms and findings. Results: Among the 111 patients with brucellosis, 69% (n = 77) had a seropositivity result for H. pylori IgG. The healthy control subjects had an 87% (n = 104) seropositivity for H. pylori IgG. The serum H. pylori IgG antibody seropositivity was significantly lower in the patients with Brucella infection compared with the control subjects ( P < 0.001). Conclusion: Our results show that the serum prevalence of H. pylori among the patients infected with brucellosis is significantly lower than that in the control population. A negative correlation between H. pylori infection and brucellosis infection might be hypothesized.